2018
DOI: 10.1111/ajgw.12352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of free fatty acids and lipolysis on Sauvignon Blanc fermentation

Abstract: Background and Aims The volatile thiols, such as 3‐mercaptohexanol, 3‐mercaptohexyl acetate and 4‐mercapto‐4‐methylpentan‐2‐one, are major aroma compounds responsible for the distinctive tropical notes (passionfruit and grapefruit) in New Zealand Sauvignon Blanc wines. Previously, it was observed that traces of linoleic acid in grape juice can significantly affect the development of these volatile thiols and other aroma compounds in wine. Here, we examined the effect of the fatty acids commonly found in Sauvig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Regarding this factor, studies such as [ 34 ] have shown significant differences in the aroma after comparing wine ageing in oak barrels and glass bottles with a trained tasting panel. However, in the current study, among these metabolites, the ones that have been connected to aromatic characteristics are palmitic acid, stearic acid, and 1-dodecanol [ 35 , 36 ] all of them having higher concentrations in the bottle-aged wines.…”
Section: Discussionmentioning
confidence: 75%
“…Regarding this factor, studies such as [ 34 ] have shown significant differences in the aroma after comparing wine ageing in oak barrels and glass bottles with a trained tasting panel. However, in the current study, among these metabolites, the ones that have been connected to aromatic characteristics are palmitic acid, stearic acid, and 1-dodecanol [ 35 , 36 ] all of them having higher concentrations in the bottle-aged wines.…”
Section: Discussionmentioning
confidence: 75%
“…Using a GC-MS-based metabolomics approach, they showed that increased concentration of linoleic acid affected different primary (e.g., amino acids) and secondary metabolites (e.g., varietal thiols and acetate esters) in a strain-specific manner. Another experiment from the same laboratory also revealed that pre-supplementation of different saturated and unsaturated fatty acids during Sauvignon blanc fermentation significantly affected the metabolism of wine yeast and as a result, end product formation [141]. These metabolomics studies together generated an awareness for the wider wine industry to select wine yeast based on the juice composition in order to obtain wines with desired aromatic profiles.…”
Section: Study Of Yeast Metabolism and Aroma Compound Development Durmentioning
confidence: 92%
“…Over the past decade, many metabolomics studies have been carried out to determine effect of juice or growth media composition on overall wine yeast metabolism, with particular attention on the developments of fermentation end products [107,108,141]. For instance, two publications from a research group of the University of Auckland reported changes before and after fermentation in Sauvignon blanc juices and how juice composition influences the major varietal aroma compound production by Saccharomyces cerevisiae EC1118 [34,107].…”
Section: Study Of Yeast Metabolism and Aroma Compound Development Durmentioning
confidence: 99%
See 2 more Smart Citations